Dynamics 365 CE Essentials Administering and Configuring Solutions - Critchley, Sarah (Apress, 2018)
Discover how to set up core Dynamics 365 Customer Engagement functionality and learn how to build more customized processes on top of the standard capabilities. This book starts by showing you how to set up the Dynamics 365 Online system for sales, customer service, marketing, field service, and Outlook integration. In the second section, you'll work through UI customizations, process automation and reporting in Dynamics 365 CE. Learn about the App Framework, how to create model-driven apps and how to get started with the Common Data Service for Apps. Leverage Microsoft Flow within Dynamics 365 CE to create loosely coupled business applications using automation from Microsoft and third-party services. After reading Dynamics 365 CE Essentials, you will have mastered the core functionality available in Dynamics 365 CE and be able to set it up for a number of different scenarios. You will: • Set up the core standard features of Dynamics 365 CE • Create model-driven apps within Dynamics 365 customized to specific business needs • Customize Dynamics 365 CE and leverage process automation functionality through the UI • Learn about the Common Data Service for Apps.